Changes in wildlife activity patterns in response to war in Ukraine - Svitlana Kudrenko; Richard Bischof; Andreas Zedrosser; Nuria Selva; Kateryna Korepanova; Denys Vyshnevskiy; Martin Gahbauer; Serhii Obrizan; Serhii Domashevskiy; Oleksandr Borsuk; Alona Varukha; Marco Heurich (Science, 2026)
Conflict zones are inherently hazardous and inaccessible for researchers, which results in a knowledge gap about the immediate effects of armed conflicts on the environment, particularly wildlife. We used camera-trap detections to investigate the impact of armed conflict on wildlife activity patterns before, during, and after the Russian occupation of the Chornobyl Exclusion Zone (Ukraine) in 2022 and compared it to the same period in 2021. Mammal species responded to armed conflict through immediate behavioral adjustments, including reduced activity during night and on dates when armed-conflict activities intensified. Our results provide insight into wildlife’s behavioral responses to armed conflict in real time and underscore the potential of camera trapping to quantify the ecological effects of war.